Calcium Chloride Treatment Patterns During Germination Influence Calcium Accumulation and Physicochemical Characteristic of of Red Rice - Maria Nurlian Turnip; Yushinta Aristina Sanjaya; Andre Yusuf Trisna Putra; Hadi Munarko (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Germination in red rice aims to improve its quality, particularly its texture. However, this germination process produces relatively long sprouts that can interfere with the quality of red rice when consumed. Therefore, calcium chloride is utilized with different application patterns to suppress sprout elongation while simultaneously enhancing calcium accumulation. Red rice (Inpari 24 variety) was germinated using a partially circulated germinator with variations in calcium chloride treatment patterns and germination duration. The physicochemical characteristics of ungerminated and germinated red rice exhibited differences, specifically in germination quality, calcium, color, pasting profile, and total sugar content. Germination without calcium chloride treatment and germination with full calcium chloride treatment at the initial stage significantly affected the germination rate, sprout length, calcium, and pasting profile of the red rice. Germination under each distinct calcium chloride application pattern successfully suppressed red rice sprout elongation. The results indicated that full calcium chloride treatment at the initial stage produced the lowest germination rate and sprout length (74.67–88.00% and 0.66–1.24 mm, respectively). Germination with calcium chloride treatment at the intermediate-stage and in a gradual manner reduced the sprout length of the red rice. The treatment with calcium chloride also increased calcium levels, an essential mineral for humans. Full treatment of calcium chloride at the initial stage yielded germinated red rice with the highest calcium (228.06–252.20 mg/100g). The different calcium chloride treatment patterns did not significantly affect the color, pasting profile, and total sugar of the germinated red rice; however, an increase was observed from the ungerminated red rice to the germinated red rice. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production